An investigation of the integrity of two components of the cerebellar neurocircuitry involved in classical eyeblink conditioning in children prenatally exposed to alcohol: a magnetic resonance spectroscopy and functional magnetic resonance imaging study - Du Plessis, Lindie (Division of Biomedical Engineering, 2015)
Includes bibliographical references.